MODEL ANALISIS SWOT DALAM PENINGKATAN KUALITAS PELAYANAN ONLINE SINGLE SUBMISSION (OSS) PADA DPMPTSP PROVINSI JAWA TIMUR - Kamelia Irfani; Firda Ainun Naziyah; Agus Widiyarta (Jurnal Administrasi Negara, 2021)
The achievement of public welfare can only be done by providing the best and optimal public services. The urgency of improving the quality of public services is actually the government's commitment so that people can get services that are easy, cheap, fast, and precise. The phenomenon of complex licensing service processes in complicated procedures and administration that takes a long time has resulted in a technology-based innovation known as Online Single Submission (OSS). This study aims to determine the strategy for improving the quality of Online Single Submission (OSS) services at DPMPTSP in East Java which is carried out by using a qualitative descriptive approach and measurement based on a SWOT analysis (Strength, Weakness, Opportunities, Threat). The results showed that the indicators of strengths include the adequacy of the quantity and quality of Human Resources (HR) of civil servants. In addition, it also relates to the program of socialization and mentoring activities which are the key strategies in improving service quality. Indicators of weaknesses were identified in security officers who also served as front office officers. In addition, there are also findings that service operating hours are less than optimal, so that a transformation strategy towards digitalization based on online connections is needed, and the creation of a civil service disciplinary supervision system. Then, the opportunities indicator describes the existence of service program innovation that is balanced with efforts to develop IT systems (e-government), However a development strategy that focuses on understanding the community through the creation of informative and educational content in order to create effective and efficient services is also urgently needed. Threat indicator states that the level of knowledge and also the ability of the community to use IT is low, so it requires a strategy to empower the community through providing IT media learning simulation.